AMP-activated protein kinase, fatty acid metabolism, and insulin sensitivity. Issue 4 (July 2017) - Smith, Brennan K.; Steinberg, Gregory R.
Abstract : Purpose of review: Insulin resistance is an important risk factor for metabolic diseases such as type 2 diabetes, cardiovascular disease and certain cancers. A common characteristic of strategies that improve insulin sensitivity involves the activation of the energy sensing enzyme of the cell, AMP-activated protein kinase (AMPK). The purpose of this review is to explore the mechanisms associated with AMPK activation to improve insulin sensitivity with a focus on fatty acid metabolism. We will also discuss the literature surrounding direct AMPK activators to improve insulin resistance and important considerations for the design of direct AMPK activators. Recent findings: AMPK activation can decrease de novo lipogenesis, increase fatty acid oxidation and promote mitochondrial integrity to improve insulin sensitivity. Drugs targeted to directly activate AMPK show therapeutic promise, yet in vivo data is lacking. Summary: Designing a drug to directly activate AMPK may improve insulin resistance by reducing liver de novo lipogenesis and increasing brown and white adipose tissue mitochondrial function. However, in vivo experimental procedures to support this notion are not extensive and more research is required.